Corporate Social Responsibility:An Integral Part of Risk Management Philosophy - Singh, Updash (2005)
The concept of Corporate Social Responsibility (CSR), the idea that businesses1 have responsibilities for their environmental performance, employee relations and social impact which goes beyond basic legal compliance has been on the corporate radar screen. That said, there are still many high profile examples of multinational companies that get it wrong, attracting negative publicity for their actions on environmental and social issues because they have failed to understand the expectations of stakeholders and the general public at large. In the past, several multinationals that have been accused of being irresponsible, for example, Shell International Ltd. for polluting the environment, The Coca-Cola Co. for food contamination, and Nike Inc. for unacceptable working conditions have paid the price and have since established CSR strategies and initiatives (Nieuwlands, 2003). Over the course of last decade, the role and accountabilities of the business world have become increasingly linked to the society within which they operate. Businesses are now under pressure to shoulder responsibilities that are not only linked to the economic development of a country or region at large, but also linked to its social development and environmental protection (Carroll & Hoy, 1996). Businesses are no longer simply expected to follow the narrow road of generating wealth but to work with government and community sectors in a more expansive social role . The shift in expectations of business is mainly accounted for by the combined factor of globalisation and the increased pressure and influence of activists and stakeholders. Businesses are being asked to consider themselves part of the surrounding communities in which they operate and therefore, to share in the responsibilities (West, 1995 and Waddock, 2004).